X‐SPEC: a 70 eV to 15 keV undulator beamline for X‐ray and electron spectroscopies. (10th February 2021) - Weinhardt, Lothar; Steininger, Ralph; Kreikemeyer-Lorenzo, Dagmar; Mangold, Stefan; Hauschild, Dirk; Batchelor, David; Spangenberg, Thomas; Heske, Clemens
Abstract : X‐SPEC is a high‐flux undulator beamline for electron and X‐ray spectroscopy with an energy range from 70 eV to 15 keV. It offers X‐ray absorption spectroscopy (XAS), extended X‐ray absorption fine structure (EXAFS), photoelectron spectroscopy (PES) and hard X‐ray PES (HAXPES), as well as X‐ray emission spectroscopy (XES) and resonant inelastic X‐ray scattering (RIXS) for in vacuo, in situ and operando sample environments. Abstract : X‐SPEC is a high‐flux spectroscopy beamline at the KIT (Karlsruhe Institute of Technology) Synchrotron for electron and X‐ray spectroscopy featuring a wide photon energy range. The beamline is equipped with a permanent magnet undulator with two magnetic structures of different period lengths, a focusing variable‐line‐space plane‐grating monochromator, a double‐crystal monochromator and three Kirkpatrick–Baez mirror pairs. By selectively moving these elements in or out of the beam, X‐SPEC is capable of covering an energy range from 70 eV up to 15 keV. The flux of the beamline is maximized by optimizing the magnetic design of the undulator, minimizing the number of optical elements and optimizing their parameters. The beam can be focused into two experimental stations while maintaining the same spot position throughout the entire energy range. The first experimental station is optimized for measuring solid samples under ultra‐high‐vacuum conditions, while the second experimental station allows in situ and operando studies under ambient conditions. Measurement techniques include X‐ray absorption spectroscopy (XAS), extended X‐ray absorption fine structure (EXAFS), photoelectron spectroscopy (PES) and hard X‐ray PES (HAXPES), as well as X‐ray emission spectroscopy (XES) and resonant inelastic X‐ray scattering (RIXS).